Psałterz poznański. Prolegomena lingwistyczne - Nowak-Barcińska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
This article discusses a collection of fifty psalms published as The Poznań Psalter. A Collection of Psalms for Common Singing at Home and in Church (Poznań 2017). As a text genre, the publication represents a song book, which – according to its dictionary definition – is: ‘a collection of songs (solemn or popular) with their lyrics and notes’. The publication can alternatively be classified as a hymnal. The authors of the paraphrased psalter intended to underscore the musical character of the Biblical texts. This musical character is underscored by giving the particular psalms their regular rhythmic pattern, partly supported with a rhyming pattern. As far as the musical layer of the Poznań Psalter is concerned, the authors make a conscious reference to tradition, since the melodic lines are transferred from the Geneva Psalter (1563 edition). The language layer, on the other hand, departs from tradition, since it does not exhibit the historically marked lexical or grammatical structures. Analysing the text of the Poznań Psalter, composed by the Protestant (Reformed Evangelical Church) authors in the context of the Polish tradition of Biblical translation, one can conclude that this tradition retains its vital interdenominational nature, which – as in the case in point – is capable of using the Warsaw Bible and the Millennium Bible as sources of textual adaptation.